Stressors and coping resources of Australian kidney transplant recipients related to medication taking: a qualitative study. Issue 11 (20th March 2017) - Low, Jac Kee; Crawford, Kimberley; Manias, Elizabeth; Williams, Allison
Abstract : Aim and objective: To understand the stressors related to life post kidney transplantation, with a focus on medication adherence, and the coping resources people use to deal with these stressors. Background: Although kidney transplantation offers enhanced quality and years of life for patients, the management of a kidney transplant post surgery is a complex process. Design: A descriptive exploratory study. Method: Participants were recruited from five kidney transplant units in Victoria, Australia. From March–May 2014, patients who had either maintained their kidney transplant for ≥8 months or had experienced a kidney graft loss due to medication nonadherence were interviewed. All audio‐recordings of interviews were transcribed verbatim and underwent Ritchie and Spencer's framework analysis. Results: Participants consisted of 15 men and 10 women aged 26–72 years old. All identified themes were categorised into: (1) Causes of distress and (2) Coping resources. Post kidney transplantation, causes of distress included the regimented routine necessary for graft maintenance, and the everlasting fear of potential graft rejection, contracting infections and developing cancer. Coping resources used to manage the stressors were first, a shift in perspective about how easy it was to manage a kidney transplant than to be dialysis‐dependent and second, receiving external help from fellow patients, family members and health care professionals in addition to using electronic reminders. Conclusion: An individual well‐equipped with coping resources is able to deal with stressors better. It is recommended that changes, such as providing regular reminders about the lifestyle benefits of kidney transplantation, creating opportunities for patients to share their experiences and promoting the usage of a reminder alarm to take medications, will reduce the stress of managing a kidney transplant. Relevance to clinical practice: Using these findings to make informed changes to the usual care of a kidney transplant recipient is likely to result in better patient outcomes.